Frequency of New Hepatocellular Carcinoma in Patients Suffering from Hepatitis C Virus Infection Related Cirrhosis Exposed to Direct Acting Antiviral-based Therapy - Ibtesaam Amjad, Junaid Mushtaq, Kanza Altaf, Ahmed Zaka Subhani, Israr-Ul-Haque Toor, Ghias-Un-Nabi Tayyab, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the frequency of hepatocellular carcinoma in patients with hepatitis C virus infection patients on dual antiviral therapy. Design of the study: Cross sectional study Settings: Department of Medicine/Division of Gastroenterology, Lahore General Hospital, Lahore. Duration: 6 months Sample Size: Sample size of 220 cases was calculated with 95% confidence level and 3.5% margin of error by taking percentage of HCC i.e. 7% in HCV patients on direct acting antiviral-based therapy. Data was analyzed with IBM-SPSS version 21. Results: In our study the mean age was 37.75±12.08 years. The mean value of duration of HCV therapy of the patients was 8.59±4.023 months. In this study the HCC was noted in 12(5.45%) patients. Conclusion: The frequency of HCC in patients with HCV infection patients on direct acting antiviral-based therapy is 5.45%.